LASERS : Spectral features and thermal resistance of 976-nm cw laser diodes with a power up to 15 W. (31st August 2016) - Bezotosnyi, V V; Krokhin, O N; Oleshchenko, V A; Pevtsov, V F; Popov, Yu M; Cheshev, E A
Abstract: The spectral characteristics of cw laser diodes with a maximum reliable power of 15 W mounted on F-mount heat sinks are studied. It is found that the spectrum envelopes have features at emission powers exceeding 5 – 7 W. A method for determining the maximum of a spectrum envelope under the conditions of its broadening and appearance of features is discussed. The thermal resistance of diodes is determined experimentally at pump currents from threshold to maximum (14 A) and is found to be 2.25 K W -1 at a current of 10 A and 1.5 K W -1 at a current of 4 A. The results obtained are compared with the literature data. The adequacy of using the thermal resistance parameter for comparing and estimating thermal characteristics of laser diodes is considered.